Hubungan Pengetahuan dan Sikap Pelajar Dengan Upaya Pencegahan HIV/AIDS di SMA Negeri 2 Raha, Kabupaten Muna - La Rangki; Firtiani Firtiani (Universitas Faletehan, 2020)
The high number of HIV / AIDS infections which continues to grow, especially among young people or teenagers, is a serious problem. Lack of knowledge and attitudes of adolescents about HIV / AIDS can influence prevention measures against HIV / AIDS. This study aims to determine the relationship of knowledge and attitudes of students with HIV / AIDS prevention efforts. The type of research used was observational analytic with cross sectional design approach. The population in this study were grade 1 students and kleas 2 students of SMA Negeri 2 Raha. While the sampling in this study using the stratified random sampling method with a total of 87 respondents. The results showed that the majority of respondents had good knowledge 63 students (72.4%) and a small proportion of respondents had less knowledge of 24 students (27.6%) and the majority of respondents had an attitude of supporting 86 students (98.9%), and a small proportion of respondents had the attitude of not supporting 1 student (1.1%) as well as respondents who did not do the prevention of 2 students (2.3%) and the majority of respondents made an effort to prevent 85 students (97.7%). There is no meaningful relationship between students 'knowledge of HIV / AIDS prevention efforts at SMA Negeri 2 Raha, but there is a significant relationship between students' attitudes towards HIV / AIDS prevention efforts. It is recommended to students to be more able to filter the information obtained, so that a positive attitude pattern is formed in the prevention of HIV / AIDS.